Expression of Surfactant Protein–A during LPS-Induced Otitis Media with Effusion in Mice. (September 2015) - Li, Li; Guo, Xiangrui; Olszewski, Emily; Fan, Zhaomin; Ai, Yu; Han, Yuechen; Xu, Lei; Li, Jianfeng; Wang, Haibo
Objective: The objective of this study was to investigate the expression and role of surfactant protein (SP) in the middle ear throughout lipopolysaccharide (LPS)-induced otitis media with effusion (OME). Study Design: Randomized case-controlled animal model. Setting: Shandong University, Jinan, China. Subjects and Methods: SP expression was monitored using reverse transcription polymerase chain reaction (PCR) in normal mice (n = 5). Two groups, control phosphate-buffered saline–injected mice (n = 5) and LPS-injected mice (n = 5), were euthanized 5 days following injection. RNA was extracted for reverse transcription PCR and real-time PCR, and temporal bone samples were used for hematoxylin and eosin staining. LPS was injected into mice, and 5 mice per test were euthanized at 0, 12, 24, 48, 72, and 96 hours following injection. For mRNA expression quantification, reverse transcription PCR and real-time PCR were performed, and proinflammatory cytokine levels were measured by enzyme-linked immunosorbent assay. Results: SP-A and SP-D expression was detected in normal murine Eustachian tubes. SP-A expression was up-regulated after LPS-induced OME ( P = .01). At various time points after LPS injection, concentrations of proinflammatory cytokines (tumor necrosis factor–α [TNF-α], interleukin (IL)–1β, and IL-6) in the middle ear increased significantly ( P < .05) and correlated with changes in SP-A expression. Conclusion: SP-A and SP-D exist in the murine middle ear. The expression of SP-A and TNF-α, IL-1β, and IL-6 was up-regulated in the middle ear of the LPS-induced OME animal model.